Edukacyjna funkcja koroplastycznych przedstawień terakotowych z Egiptu okresu grecko-rzymskiego, na podstawie wybranych grup zabytków - Jędraszak, Sławomir (Biuletyn Historii Wychowania, 2015)
The Educational Function of Terracotta Representations from Egypt in the Graeco-Roman Period The subject of this paper aims to investigate problems associated with selected examples of terracotta drawn from the wide iconographic range of figurines produced in Egypt during the Graeco-Roman period. It attempts to find an answer to the question of whether, in the case of the categories of figurines and terracotta plaques, there are any associations or correlations with upbringing and education. The author maintains that the terracotta figurines, which are the subject of this paper, could include, among many others, examples evoking patterns of appropriate behaviour. Some figurines also played a significant part in the history of Graeco-Roman Egypt, forming an important source for the promotion of a range of information with a socio-political content.